Are some brightly coloured European wild birds toxic? - Loxdale, Hugh D. (Frontiers in Ecology and Evolution, 2023)
Some colourful European wild birds with contrasting bright colours, often striking black and white vs. a primary and secondary colour/s, and with the same basic plumage livery shared by both sexes, are very obvious to would-be predators when they forage diurnally, or continue other aspects of their life history, including courting, nest building and rearing their brood. Here, I posit that such birds may be displaying aposematic warning colouration, possibly enhanced by chemical noxious substances in their flesh and/or feathers, as is already known in some bird species, including colourful as well as cryptic species. The warning colouration may be Müllerian or Batesian in nature, or maybe is a ruse to suggest to predators that they are in some way noxious, and thus to be avoided. Even if not actually noxious as such, this may give the intended prey species time to escape. Certainly, birds like the very obviously blue-black and white patterned Eurasian magpie, Pica pica, are generally avoided by raptorial birds such as the sparrow hawk. These various possibilities are discussed in the present article.